Effect of Acetic Acid and Propanoic Acid on Ethanol Fermentation by Saccharomyces cerevisiae in an Ethanol-Methane Coupled Fermentation Process - Zhang, C.M.; Zhang, J.H.; Tang, L.; Mao, Z.G.; Zhu, R.S.; Zhang, H.J. (Asian Journal of Chemistry, 2011)
Waste distillage can be fully recycled in an ethanol-methane coupled fermentation process. In this process, waste distillage from ethanol fermentation was first treated in an anaerobic digestion and then the effluent used for the next ethanol fermentation batch. Organic acids, mainly acetic acid and propanoic acid, contained in the effluent could potentially inhibit the ethanol fermentation. The effects of organic acids on ethanol fermentation were investigated in this study. Results indicated that, to avoid ethanol fermentation inhibition, aceticacetic acid and propanoic acid in the medium should be < 80 and < 30 mM, respectively. Interestingly, ethanol production increased 20 and 13 % in the presence of 20 mM of aceticacetic acid and propanoic acid, respectively. Decreased by-product production, biomass and glycerol could have contributed to the increased ethanol production.